PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PEMALSUAN KARTU KREDIT (STUDI PUTUSAN No.345/PID.SUS/2021/PNY-YK): Criminal Against The Criminal Action Of Credit Card Forgery (Verdict Study N0. 345/Pid.Sus/2021/PNYyk) - Setiawan, R Andhika Prameswara; Ganarsih, Yenti (AMICUS CURIAE, 2024)
The crime of credit card forgery committed by Faisal Umar Firmansyah Bin Farid Firmansyah, namely  the act of buying another person's CC (Credit Card) without the knowledge of the owner at a price of IDR 80,000 per credit card and purchasing 9 (nine) cellphones by checking whether registered in the KLARNA application and if registered and have a balance then the purchase will continue and if there is no balance in the KLARNA application then fill it in advance for every $1000 USA at a price of IDR 3,000,000 to IDR 5,000,000 .Research with Decision Study No.345/Pid.sus/2021/Pn.Yyk. and there is a formulation of the problem: 1. Is the court's decision against the convict's actions Credit Card Counterfeiting according to Ps. 32 paragraph (1) jo. Ps 48 paragraph (1) Law no. 19 of 2016 concerning Amendments to Law no. 11 of 2008 concerning Electronic Information and Transactions? This study uses a normative research type that is descriptive analytical, using literature or secondary data which consists of primary legal materials and secondary legal materials obtained from literature studies and analyzed qualitatively using deductive logic, as well as drawing conclusions. The conclusions from this study are that 1. The Court's decision given to the Defendant of the Crime of Credit Card Counterfeiting is not appropriate based on Article 32 paragraph (1) jo. Ps 48 paragraph (1) Law no. 19 of 2016 concerning Amendments to Law no. 11 of 2008 concerning Information and Electronic Transactions, and 2. Judge's Decision No. 345/Pid.Sus/2021/PN Yyk which imposes a criminal sanction of 6 (six) months in prison is not in accordance with the purpose of sentencing.